Antibiotic Adjuvants from Natural Resources against Multi-Drug Resistance Bacteria - Febrimarsa, Febrimarsa; Hatini, Lutfiah; Herabare, Regita Aulia; Sofia, Revina Gina (Universitas Muhammadiyah Surakarta, 2025)
The rise of multi-drug resistant bacteria signals the end of the antibiotic era, a global threat confirmed by the World Health Organization. Bacteria have evolved sophisticated resistance mechanisms, such as target modification, enzymatic drug inactivation, efflux pumps, and biofilm formation, which render many first-line antibiotics ineffective. In response, combination therapy has emerged as a critical strategy, historically proven effective in treating infections caused by pathogens like Mycobacterium tuberculosis and Helicobacter pylori. This paper explores the use of natural compounds as antibiotic adjuvants to enhance or restore the efficacy of existing antibiotics. The success of Clavulanic Acid, a natural product combined with amoxicillin, serves as a prime example of this approach. Investigating the vast biodiversity of natural resources, such as those found in Indonesia, offers a promising avenue for discovering novel adjuvants. While numerous in vitro studies have identified promising combinations, translating these findings into successful animal models and clinical therapies remains a significant challenge.